Pengaruh Pemeriksaan Pajak dan Self Assessment System terhadap Tax Evasion Pada Kantor Pelayanan Pajak Pratama Bekasi Barat - Firda Al Liyanda; Ratih Kumala (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
There are targets and realizations at the Small Tax Office of West Bekasi, which experienced significant fluctuations. This is caused by the taxpayers who still manipulating tax data or attempting to commit tax evasion. This study aims to determine the effect of tax audits and self-assessment systems on tax evasion at the Small Tax Office of West Bekasi. The research method used is quantitative methods and data collection techniques in the form of a questionnaire with a Likert scale. The research population is taxpayers registered at Small Tax Office of West Bekasi who have reported the annual corporate income tax return and conducted tax audits, with a total of 99 samples. The sampling technique used is a simple random sampling technique. Data analysis was done by multiple linear regression analysis using SPSS V.21 application. The results showed that there was a significant effect between tax audit and selfassessment systems on tax evasion with tcount > ttable. Meanwhile, based on the results of the simultaneous test of tax audits and the self-assessment system together, they have a positive and significant effect on tax evasion with the results of Fcount > Ftable. The determination coefficient test of 27.2% of the tax evasion variable can be explained by the variation of the two independent variables and the remaining 72.8% is influenced by other variables outside of this study.